Characterization and Analysis Kombucha Tea Antioxidant Activity Based On Long Fermentation as a Beverage Functional - Nurikasari, Maulina; Puspitasari, Yenny; Siwi, Retno Palupi Yoni (Universitas STRADA Indonesia, 2017)
Kombucha is a symbiosis between bacteria (Acetobacter) and yeast (Saccharomyces), in English abbreviated SCOBY (Symbiotic Culture of Bacteria and Yeast). SCOBY in this research will be fermented using green tea media, to make kombucha tea product. Kombucha tea content is very beneficial for health, such as vitamin B1 (thiamine), vitamin B2 (riboflavin), vitamin B3 (niacin), vitamin B12 (cyanocobalamin), vitamin C, acetic acid, amino acids, glucoronic acid, lactic acid and antiocasidan. Product characteristic is needed to produce good product quality. The researchers used experimental studies and used the RAL method by varying the length of fermentation of kombucha tea. The result of characterization, kombucha tea pH the longer the fermentation time decreases, the longer the fermentation time the more bright, the weight of cellulose produced SCOBY more fermentation time increases weight, the reduction of sugar content the longer the fermentation time will decrease. The optimum antioxidant activity was obtained on the 7th day of fermentation of 93.79%. Based on the results and the above discussion can be concluded, the color will be brighter with increasing length of fermentation, as well as the weight will increase with the longer fermentation. In contrast to the pH and sugar reductions the longer the fermentation time will decrease. The antioxidant activity had an optimum point on 7th day fermentation of 93.79% and will decrease with increasing fermentation time.